Pursuing computationally efficient wear-out prediction of PV inverters: The role of the mission profile resolution. (July 2020) - Silva, R.P.; de Barros, R.C.; Brito, E.M.S.; Boaventura, W.C.; Cupertino, A.F.; Pereira, H.A.
Abstract: Over the last decades, the connection of photovoltaic (PV) plants into the grid has increased. In this context, the analysis of the PV inverter reliability became a target of study for many researchers in the area. The solar irradiance and ambient temperature mission profiles are highly used in the literature to perform the PV inverter lifetime evaluation. However, the choice of the mission profile resolution is not straightforward. The increasing of the mission profile sampling time can reduce the consumed simulation time during the lifetime evaluation process. Nevertheless, the evaluation accuracy decreases. Therefore, this work analyzes the effect of the mission profile resolution for the semiconductor devices and the electrolytic capacitors, separately. A maximum allowed error equals 10% in the obtained lifetime consumption is assumed. For the case study analyzed in this work, the total processing time was reduced in 27.91% for a lifetime evaluation error lower than 9%. Highlights: Mission proﬁle resolution which reduces the computational burden without signiﬁcantly aﬀecting the reliability prediction. Analysis of the PV inverter lifetime consumption considering long and short-cycles evaluations. Lowest mission proﬁle resolution identification with which the desired target error of the lifetime consumption is reached. Lifetime consumption evaluation in system-level considering diﬀerent ways to decimate the mission proﬁle.